Improved radiocarbon dating for contaminated archaeological bone collagen, silk, wool and hair samples via cross‐flow nanofiltrated amino acids. (13th August 2013) - Boudin, Mathieu; Boeckx, Pascal; Vandenabeele, Peter; Van Strydonck, Mark
Abstract : RATIONALE: Radiocarbon dating and stable isotope analyses of bone collagen, wool, hair and silk contaminated with extraneous carbon (e.g. humic substances) does not yield reliable results if these materials are pre‐treated using conventional methods. METHODS: A cross‐flow nanofiltration method was developed that can be applied to various protein materials like collagen, hair, silk, wool and leather, and should be able to remove low‐molecular and high‐molecular weight contaminants. To avoid extraneous carbon contamination via the filter a ceramic filter (molecular weight cut‐off of 200 Da) was used. The amino acids, released by hot acid hydrolysis of the protein material, were collected in the permeate and contaminants in the retentate (>200 Da). RESULTS: 14 C‐dating results for various contaminated archaeological samples were compared for bulk material (pre‐treated with the conventional methods) and for cross‐flow nanofiltrated amino acids (permeate) originating from the same samples. Contamination and quality control of 14 C dates of bulk and permeate samples were obtained by measuring C:N ratios, fluorescence spectra, and δ 13 C and δ 15 N values of the samples. Cross‐flow nanofiltration decreases the C:N ratio which means that contaminants have been removed. CONCLUSIONS: Cross‐flow nanofiltration clearly improved sample quality and 14 C results. It is a quick and non‐labor‐intensive technique and can easily be implemented in any 14 C and stable isotope laboratory for routine sample pre‐treatment analyses. Copyright © 2013 John Wiley & Sons, Ltd.